A framework for assessing quality of a web site - Vamsi Krishna, M; Kiran Kumar, K; Sandiliya, CH; Vijaya Krishna, K (International Journal of Engineering and Technology, 2018)
The greater part of the data spread is occurring through Web locales and Web gateways. The adequacy and effectiveness with which data can be spread is especially reliant on the nature of the WEB webpage. The more the nature of a site/entryway, the more refined data can be made accessible to the client. In this manner it ends up noticeably important to characterize quality and furthermore decide the components that measure the nature of site. A quality factor should stick point to a specific part of the web architecture. It is additionally essential to characterize the sort of change that must be attempted for enhancing nature of the site from the perspective of a specific angle.This paper is principally cantered around deciding terrifically imperative quality factors that can consolidated mirror the aggregate quality and in addition nature of a specific part of web composition. This paper additionally gives a base utilizing which various types of upgrades that ought to be made all together that the nature of the Web website will significantly be improved. Websites are a piece of our regular day to day existence and are utilized to trade and to pass on data between client groups. Passed on data comes in various kinds, dialects and shapes and fuses content, pictures, sound, and video expected to illuminate, induce, offer, show a perspective or even change a demeanour or conviction. Regardless of site multiplication, appraisal of site quality remains a testing region of research. Quality identifies with consumer loyalty and furthermore with the level of achievement of client desire while interfacing a site.